Mpox infection in people with HIV: a case series in a nonendemic country - Mohd Taib, Niazlin; Masri, Siti Norbaya; Madon, Mazriza; Abdul Rashid, Fairuz; Badarol Hisham, Noralwani (Universiti Putra Malaysia, 2024)
Introduction: Mpox is a zoonotic viral infection caused by an enveloped double-stranded deoxyribonucleic acid (DNA) monkeypox virus (MPXV). It is endemic in Central and West Africa, but global mpox outbreak has been declared by World Health Organization (WHO) as a Public Health Emergency of International Concern (PHEIC) following the escalation of cases in non-endemic countries in July 2022. This outbreak has been associated with con- comitant human immunodeficiency virus (HIV) and sexually transmitted disease, involving primarily gay, bisexual and men who have sex with men (MSM). Case series: This is a case series of mpox in people living with HIV in a non-endemic locality, which were confirmed by detection of MPXV DNA by polymerase chain reaction (PCR) from the lesion swabs. The clinical manifestations and transmission routes of mpox virus (MPXV) infection in immuno- compromised individuals, especially in non-endemic regions, remain poorly understood. The case series highlights the different clinical manifestation and routes of transmission of MPXV in immunodeficient patients, particularly in people with HIV. Conclusion: This case series can provide healthcare practitioners and the public with insights into identifying the clinical manifestations of mpox and the vulnerable groups, thereby improving screening efforts and helping to curb the transmission of the infection in a non-endemic country.